Amorphous solid dispersion enhances permeation of poorly soluble ABT-102: true supersaturation vs. apparent solubility enhancement - Frank, Kerstin J.; Fricker, Gert (International journal of pharmaceutics, 2012)
Amorphous solid dispersions (ASDs) represent a promising formulation approach for poorly soluble drugs. We explored the formulation-related impact of ASDs on permeation rate, apparent solubility and molecular solubility of the poorly soluble drug ABT-102. The influence of fasted state simulated intestinal fluid (FaSSIF) as dispersion medium was also studied. ASDs were prepared by hot-melt extrusion. Permeation rate was assessed by the Caco-2 transwell assay. Cell viability and barrier integrity were assured by AlamarBlue©, TEER and permeability of the hydrophilic marker carboxyfluorescein. Apparent solubility and molecular solubility were evaluated by using centrifugation and inverse dialysis, respectively. The in vitro permeation rate of ABT-102 from aqueous dispersions of the ASD was found 4 times faster than that from the dispersions of the crystals, while apparent solubility and molecular solubility of ABT-102 were increased. Yet, a further increase in apparent solubility due to micellar solubilization as observed when dispersing the ASD in FaSSIF, did not affect molecular solubility or permeation rate. Overall, a good correlation between permeation rate and molecular solubility but not apparent solubility was seen.
Gesehen am 23.04.2018